2022
DOI: 10.1021/acsphotonics.2c01035
|View full text |Cite
|
Sign up to set email alerts
|

Excitons at the Phase Transition of 2D Hybrid Perovskites

Abstract: 2D halide perovskites are among intensely studied materials platforms profiting from solution-based growth and chemical flexibility. They feature exceptionally strong interactions among electronic, optical, as well as vibrational excitations and hold a great potential for future optoelectronic applications. A key feature for these materials is the occurrence of structural phase transitions that can impact their functional properties, including the electronic band gap and optical response dominated by excitons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 58 publications
3
19
1
Order By: Relevance
“…The exciton binding energy is then readily determined by Eb = Eg -E1s, where E1s is the resonance energy of the 1s exciton taken from the exciton absorption peak. The resulting Eb measurement of 256 ± 4 meV is about half the value of most reports from the literature [3][4][5][6] . Before studying the variation in Eb between different materials, we first investigate whether this measurement method is affected by the polycrystalline nature of the thin films (which is necessitated by our EA geometry) by comparing the BA2PbI4 thin film absorption to that of a single crystal.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…The exciton binding energy is then readily determined by Eb = Eg -E1s, where E1s is the resonance energy of the 1s exciton taken from the exciton absorption peak. The resulting Eb measurement of 256 ± 4 meV is about half the value of most reports from the literature [3][4][5][6] . Before studying the variation in Eb between different materials, we first investigate whether this measurement method is affected by the polycrystalline nature of the thin films (which is necessitated by our EA geometry) by comparing the BA2PbI4 thin film absorption to that of a single crystal.…”
Section: Resultsmentioning
confidence: 53%
“…The last decade has seen significant research interest in monolayer transition metal dichalcogenides (TMDC) and 2D halide perovskites (HP) due largely to unique and tunable properties of the 2D Wannier excitons that are hosted in these systems 1,2 . However, the large variance in reported Eb for the same material, e.g., 180 -490 meV [3][4][5][6][7][8] for BA2PbI4 (where BA = butylammonium), forces one to conclude that either Eb is highly dependent on sample/extrinsic conditions or else Eb measurement methods are less trustworthy as is often assumed.…”
Section: Introductionmentioning
confidence: 99%
“…This improved crystal growth is also observable in the relating PL spectra (Figure 1(g)), illustrating higher peak intensity at 517 nm for RPP layers prepared at higher temperatures. This main PL peak (at 517 nm) is attributed to emissive free excitons in the prepared RPP layers [1,33]. However, we proved that room temperature spin coating has led to layers with rough surfaces in parts (a, b, d, e), which correspond to a secondary radiative recombination PL peak at 538 nm in Figure 1(g).…”
Section: Resultsmentioning
confidence: 80%
“…The role of the organic cations on phonon and exciton dynamics in quasi-2D RP perovskites has been studied in several experimental and theoretical studies. The coupling between thermal vibrations and optoelectronic properties in RP perovskites was studied by several authors and shown to lead to phonon-assisted scattering, charge-carrier screening, and charge-carrier localization. Quan et al showed that the pronounced anharmonicity of BA 2 PbI 4 induced by the organic spacers leads to enhanced phonon scattering rates and facilitates vibrational relaxation coupled to photogenerated excitations . Furthermore, differential scanning calorimetry and X-ray diffraction measurements by Dahod et al revealed a reversible phase transition associated with a partial melting of organic spacers in BA-based RP perovskites with higher inorganic layer thickness .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, differential scanning calorimetry and X-ray diffraction measurements by Dahod et al revealed a reversible phase transition associated with a partial melting of organic spacers in BA-based RP perovskites with higher inorganic layer thickness . While the dynamic distortions markedly influence the free carrier masses and drift-diffusion transport mechanisms, they do not affect the exciton binding energies and exciton diffusion in quasi-2D RP perovskites . Thermal transport properties of quasi-2D RP perovskites have come into focus only recently, when several experimental and theoretical studies ,, reported ultralow thermal conductivities in A 2 PbX 4 (A = BA, PEA, X = I, Br) using thermal reflectance measurements combined with molecular dynamics simulations based on a classical force field.…”
Section: Introductionmentioning
confidence: 99%